Los desafíos éticos en la globalización - Debeljuh, Patricia (2017)
The globalization extends with great speed and complexity, affecting economic, cultural and social order of the countries. This phenomenon can be a great growth opportunity for businesses but in turn, it could become a threat to those who have not developed a strong culture focused on values. In this context, the aim of this article is to reflect on the importance of ethics in globalization and it discusses some initiatives of global ethics codes. The global ethical codes are those that mark the way and the way of doing business so that globalization becomes an instrument for developing countries.